International Cooporation in Criminal Procedure for Globalization and International Intergration - Chi, Nguyen Ngoc (VNU Journal of Science: Legal Studies; Vol 34 No 2, 2018)
Based on the right to international cooperation in criminal procedure, the article discusses both the theoretical and practical aspects of criminal procedure towards improving the efficiency of international cooperation in criminal procedure in the context of globalization and international integration in Vietnam. Specifically, the article discusses the common areas of international cooperation in criminal procedure; the practice of international cooperation in criminal procedure in Vietnam; the requirements posed by the context of international integration for improving the law and the effectiveness of international cooperation in criminal procedure. Keywords International cooporation, criminal procedure, extradition, judical assistance, convict transfer, transfer of sentenced persons. References [1] Christopher L. Blakesley “The Practice of Extradition from Antiquity to Modern France and the United States: A BriefHistory 4 B.C. Int'l & Comp. L. Rev. 39 (1981)” http://lawdigitalcommons.bc.edu/ iclr/vol4/iss1/3. [2] Nguyễn Trung Tín, “Dẫn độ trong Luật Hình sự Quốc tế”, trong sách Những vấn đề lí luận và thực tiễn về Luật hình sự quốc tế, Nxb Chính trị quốc gia, năm 2013. [3] Nguyễn Thị Ly, Luận văn thạc sĩ luật học, “Chế định dẫn độ trong hợp tác quốc tế theo luật tố tụng hình sự Việt Nam”, năm 2015. [4] Nguyễn Hòa Bình, sách chuyên khảo “Những nội dung mới của Bộ luật Tố tụng Hình sự năm 2015”, Hà Nội năm 2016, Nxb Chính trị Quốc gia, tr.383. [5] Báo cáo tổng kết 06 năm thi hành Luật tương trợ tư pháp trong lĩnh vực dẫn độ, chuyển giao người bị kết án phạt tù của Bộ Công an ngày 31/07/2014. [6] Vũ Quốc Thắng, “Một số vấn đề thực tiễn về tương trợ tư pháp hình sự trong các vụ án có yếu tố nước ngoài” tạp chí Kiểm sát, số 24, tháng 12 năm 2014. [7] Báo cáo tổng kết công tác thực hiện tương trợ tư pháp của VKSNDTC các năm. [8] William Y.W.Loo, Legal analyst, “Trend in Mutual Legal Assistance and Asset recovery in Asia and the Pacific” in Asset recovery and mutual legal assistance in Asia and the Pacific. [9] Annex for ASEAN Security Community Plan of Action. Nguồn: http://www.aseansec.org. [10] Supreme Prosecutors’ Office Republic of Korea, International cooperation, truy cập đường link: http://www.spo.go.kr/. Ngày truy cập: 31/3/2018 [11] Nghị quyết Ðại hội lần thứ XII của Ðảng. [12] Kimberly Prost, Breaking down the barriers: Inter-National Cooperation in Combating Transnational Crime.